1989
DOI: 10.1007/bf00043352
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic, cytogenetic, and enzymatic variation in tissue culture regenerated plants of apomictic old-world bluestem grasses (Bothriochloa sp.)

Abstract: Somaclonal variant plants may be of use in broadening the germplasm base of plant species and providing useful stocks for cytogenetic investigations. This study was conducted to compare morphologic, cytogenetic and enzymatic characteristics of 21 R~ (initial regenerate) bluestem, Bothrioehloa sp., plants, visibly identified in a field-grown population of 522 plants as probable variants, with their respective R 0 (explant donor) progenitor. An R, seedling population was grown to ascertain the transmission of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The expression of somaclonal variation in apomictic grasses appears to be species dependent. Taliaferro et al (1989) reported variability in regenerants of two Bothriochloa species but Hanna et al (1984) did not find variability in regenerants of apomictic Panicum maximum Jacq.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of somaclonal variation in apomictic grasses appears to be species dependent. Taliaferro et al (1989) reported variability in regenerants of two Bothriochloa species but Hanna et al (1984) did not find variability in regenerants of apomictic Panicum maximum Jacq.…”
Section: Introductionmentioning
confidence: 99%
“…Davies and Cohen (1992) found alterations in apomictic seed production among dallisgrass somaclones, and progeny derived from some somaclones were not uniform in phenotype. In contrast, Taliaferro et al, (1989) found uniform expression of somaclonal variation in the progeny of somaclones, confirming genetic transmission of somatic variation in floral morphology, plant height, foliage colour, and fertility in apomictic bluestem (Bothriochioa sp.) somaclones.…”
Section: Somaclonal Variation In Forage Grassesmentioning
confidence: 68%
“…comm.). These grasses exhibit an apomictic mode of reproduction (Taliaferro et al 1989). These grasses exhibit an apomictic mode of reproduction (Taliaferro et al 1989).…”
Section: Somatic Embryogenesis In Bluestem Grasses (Bothriochloa Specmentioning
confidence: 99%
“…An alternate approach for the improvement of crop plants, especially the apomicts (Taliaferro et al 1989) is to select tissue culture-induced mutants or somaclonal variants showing useful characters. In our laboratory, attempts are now in progress to develop a genetic transformation protocol in which transgenic Caucasian bluestem plants can be regenerated using this rapid regeneration system.…”
Section: Applicationsmentioning
confidence: 99%